1992
DOI: 10.1902/jop.1992.63.4.274
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Healthy and Diseased Periodontal Sites in Poorly Controlled Insulin Dependent Diabetics

Abstract: A group of poorly‐controlled insulin dependent diabetes mellitus (IDDM) patients were examined in a cross‐sectional design for total microbial levels, microbial incidence, and the percent levels of selected periodontal microorganisms. These organisms were selected on the basis of prior reports that associated them with either periodontal disease or health. One periodontally‐healthy and one periodontally‐diseased site were examined in each IDDM patient. Increased levels of the periodontal pathogens Prevotella i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
4

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 63 publications
1
32
0
4
Order By: Relevance
“…3,7,8,9 However, there are conflicting findings which have shown that poorly controlled insulindependent individuals with DM may have elevated levels of microbiota, 10 lower prevalence of pathogenic species, 8 or even a microbiota similar to that of non-DM individuals. 2,11 Differences among studies may be explained by the metabolic control used.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,8,9 However, there are conflicting findings which have shown that poorly controlled insulindependent individuals with DM may have elevated levels of microbiota, 10 lower prevalence of pathogenic species, 8 or even a microbiota similar to that of non-DM individuals. 2,11 Differences among studies may be explained by the metabolic control used.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…So that bias would be avoided, none of those variables underwent any alteration during However, those with DM2 presented significantly higher bacterial levels of C. rectus and P. gingivalis compared with SH individuals. Mandell et al 10 also observed increased levels and prevalence of C. rectus, as well as other periodontal pathogens, at diseased sites in those with poorly controlled insulindependent DM. Other species, such as P. gingivalis, A. actinomycetemcomitans, Campylobacter spp., Capnocytophaga spp., and Eubacterium nodatum, can be detected at high frequency in those with DM.…”
mentioning
confidence: 91%
“…El análisis del PCR de nuestra investigación muestran una alta presencia de Treponema denticola y Tannerella forsythia, seguida de Porphyromonas gingivalis y Aggregatibacter actinomycetemcomitans (Tabla 5). Estos resultados son similares a los obtenidos por Makiura y cols (29) , sin embargo contrastan con otros estudios que detectaron mayor presencia de Porphyromonas gingivalis que de Treponema denticola y Aggregatibacter actinomycetemcomitans (30)(31)(32)(33) . Al analizar la presencia de las bacterias estudiadas según severidad de la periodontitis, Treponema denticola, Tannerella forsythia y Porphyromonas gingivalis se presentaron en mayor porcentaje en los sujetos con periodontitis moderada y severa.…”
Section: Discussionunclassified
“…Al analizar la presencia de las bacterias estudiadas según severidad de la periodontitis, Treponema denticola, Tannerella forsythia y Porphyromonas gingivalis se presentaron en mayor porcentaje en los sujetos con periodontitis moderada y severa. La prevalencia de Porphyromonas gingivalis en nuestra investigación fue inferior a lo obtenido por otros autores, tanto en pacientes sistémicamente sanos (34,35) , como en diabéticos (10,(31)(32)(33) . Se ha observado que la proporción de especies como Porphyromonas gingivalis, Treponema denticola y Tannerella forsythia aumenta a medida que los valores de profundidad al sondaje son mayores (34) , lo que está en concordancia con lo observado en nuestro estudio en que el grupo de pacientes con periodontitis severa presentó mayor presencia de Porphyromonas gingivalis comparado con los grupos de periodontitis leve y moderada.…”
Section: Discussionunclassified
“…Some studies report differences between groups of patients with long-lasting and correctly managed monitoring of glycaemia and those with an insufficiently monitored and managed course of glycaemia. Increased amounts of periodontal microbial pathogens were confirmed in diabetic patients but their microbial strains were no different from those of non-diabetic patients (Mandel et al 1992;Zambon et al, 1988;Straka, 2011).…”
Section: Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 99%